KOALISI PARTAI ISLAM DI INDONESIA PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 - Ekawati, Esty (Jurnal Penelitian Politik, 2016)
Political coalition is a necessity for a state, like Indonesia, that using multiparty system. Coalition is a must since the election could not provide a majority in a parliament. Some factors have determined the parties’ political behavior in Indonesia and present two factors that would determine why were the coalition of Islamic political parties difficult to realize in the 2014 Presidential election. Firstly, political pragmatism has made Islamic polical party become cartel party in which party become agent of the state and employs the resources of the state to ensure the survival of the party. Secondly, Islamic political parties do not have popular figures against Prabowo and Jokowi.